PENDAMPINGAN ETIKA LITERASI MENJADI ADMIN MEDIA SOSIAL PEMERINTAH YANG BIJAK DI PALEMBANG - Santoso, Budi; Herfriady, Herfriady (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2021)
Abstract Social media has become an arena for throwing issues at each other until in the end people are bombarded with various information whose source and truth are unclear. The lack of awareness of creating comfort and peace for the community through the use of healthy information prompted the birth of this community service program. The youth of RT 1 Kelurahan Mokoau as the target of the activity should be able to become the driving force of information democracy but in fact the understanding in consuming and disseminating information as well as the ability to select and produce quality information is still limited. The lack of ethics in social media encourages the birth of hoax news, hate speech and bullying which is currently happening a lot. Through this partnership-oriented service activity, it will be a solution to this problem. This solution is carried out through training activities to form partners' understanding and knowledge of the use of social media. After the training activities, there has been a change in partners' understanding and ability to recognize and identify social media content that contains hoaxes, hate speech and bullying. Awareness in controlling the use of social media in terms of updates, shares and likes on social media is starting to grow. Apart from being documented on video, this activity has also been published in online news media. Through this PKM program, a healthy youth social movement using social media was born as a form of responsibility in minimizing the occurrence of misuse of information in society with the Instagram account @antihoaxandhatespeech and Facebook @antiHoax Bullying.